Interaction Analyses of 14-3-3ζ, Dok1, and Phosphorylated Integrin β Cytoplasmic Tails Reveal a Bi-molecular Switch in Integrin Regulation. Issue 21 (19th October 2018) - Chatterjee, Deepak; D'Souza, Areetha; Zhang, Yaming; Bin, Wu; Tan, Suet-Mien; Bhattacharjya, Surajit
Abstract: Integrins are hetero-dimeric (α and β subunits) type I transmembrane proteins that facilitate cell adhesion and migration. The cytoplasmic tails (CTs) of integrins interact with a plethora of intra-cellular proteins that are required for integrin bidirectional signaling. In particular, the β CTs of integrins are known to recruit a variety of cytosolic proteins that often have overlapping recognition sites. However, the chronological sequence of β CTs/cytosolic proteins interactions remains to be fully characterized. Previous studies have shown that the scaffold protein 14-3-3ζ binds to phosphorylated β CTs in activated integrins, whereas interactions of Dok-1 with phosphorylated β CTs maintained integrins in the resting state. In this study, we examined the binding interactions between 14-3-3ζ, Dok1, and phosphorylated integrin β2 and β3 CTs. We show that the scaffold protein 14-3-3ζ interacts with the phosphotyrosine binding (PTB) domain of Dok1 even in the absence of the phosphorylated integrin β CTs. The interactions were mapped onto the β-sheet region of the PTB domain of Dok1. Furthermore, we provide evidence that the 14-3-3ζ/Dok1 binary complex is able to bind to their cognate phosphorylated sequence motifs in the integrin β CTs. We demonstrate that Thr phosphorylated pTTT β2 CT or pTST β3 CT can bind to 14-3-3ζ that is in complex with the Dok1 PTB domain, whereas Ser phosphorylated β2 CT or Tyr phosphorylated β3 CT interacted with Dok1 in 14-3-3ζ/Dok1 complex. Based on these data, we propose that 14-3-3ζ/Dok1 complex could serve as a molecular switch providing novel molecular insights into the regulating integrin activation. Graphical Abstract: Highlights: Beta cytosolic tails (β CTs) of integrins bind to repressors and activators. How repressors and activators could aptly switch positions is not clearly understood. Activator 14-3-3ζ and repressor Dok1 form a binary complex. 14-3-3ζ/Dok1 complex acts as a switch toward recognition of phosphorylated β CTs. A novel mode of integrin regulation is presented.